International Students in Times of Corona in the United States: A Duoethnography of Foreignness (Comparative & International Education Series, 2021)
The COVID-19 pandemic has become a representation of different countries and cultures. In the U.S., it seemed to assert American elitism and white supremacy. The “go back to your country” trope became rampant, and Asians in the U.S. scrambled to ensure their health and safety both from the virus and from the social response it unleashed. Higher education was profoundly affected by COVID-19 and associated challenges. This volume has likely addressed the educational, financial, and political ramifications of COVID-19 on higher education. However, missing from the conversation are stories representing experiences of internationals. This chapter is a duoethnography about foreignness, demonstrating how COVID-19 in the U.S. perpetuated a postcolonial ideology that impacts the experiences of those deemed foreign by western standards. We use our lived experiences and narrative to illustrate how COVID-19 did not create this sense of foreignness, but intensified its presence and effects.How to cite:Xie, W., & Shaheen, M. (2022). International students in times of corona in the United States: A duoethnography of foreignness. In J. S. McKeown, K. Bista, & R. Y. Chan (Eds.), Global higher education during COVID-19: Policy, society, and technology (pp. 167-183). STAR Scholars. https://starscholars.org/product/global-education/